Advanced Eco-Friendly Wood-Based Composites II - Reh, Roman; Kristak, Lubos; Lubis, Muhammad Adly Rahandi; Lee, Seng Hua; Antov, Petar (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The ongoing twin transition of the wood-based panel industry towards a green, digital, and more resilient bioeconomy is essential for a successful transformation to decarbonize the sector and implement a circular development model, transforming linear industrial value chains to minimize pollution and waste generation, and providing more sustainable growth and jobs. This green transition represents an opportunity to place the wood-based panel industry on a new path of more sustainable and inclusive growth, tackling climate change and reducing its dependence on fossil-derived raw materials, thus improving the industry's resource efficiency and security. It provides examples of the most recent advances and technological developments in the design, production, characteristics, and current and future applications of sustainable, eco-friendly wood and wood-based composites with enhanced properties and a reduced carbon footprint. It is intended for material scientists, wood scientists, environmental scientists, graduate and postgraduate students in Wood Science and Technology, as well as wood-based panel industry professionals. In addition, the content is relevant to government authorities and stakeholders working in the domain of sustainable wood value chains, aimed at achieving Sustainable Development Goals and enhanced contribution of the forest-based sector to long-term climate change mitigation.